THE EFFECTS OF SENTENCE STRUCTURE AND VOCABULARY MASTERY ON STUDENTS’ WRITING SKILL IN RECOUNT TEXT - Iwan Ridwan (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2017)
The objective of this research is to find out the Effects of Sentence Structure and Vocabulary Mastery on Students’ Writing Skill in Recount Text at State Junior High School in Eastern Karawang. Survey was applied in this research with 60 samples which have been analyzed by descriptive statistic to find out mean, median, mode, deviation standard, and inferential statistic to find out correlation and regression, ttestand Ftestfor significant correlation and regression. This research has been done in two State Junior High Schools in Eastern Karawang. The result of hypothesis test was gained as follows: 1) There are significant effects of sentence structure (X1) and vocabulary mastery (X2) on students’ writing skill in recount text (Y). It can be seen from the result of the multiple regression where the multiple correlation coefficient (R) is 0,426. It is obtained that Fobserved is 21,512 and Sig.= 0,000 < 0,05 . 2) There is effect of sentence structure mastery (X1) on students’ writing skill in recount text (Y). The result is supported by the number of correlation coefficient of X1 to Y is 0,426. It is obtained that tobserved is 2,801 > ttable = 0,254 and Sig.0,007 < 0,05. 3) There is  effect of vocabulary mastery (X2) on students’ writing skill in recount text (Y). The result is supported by the number of correlation coefficient of X2 to Y is 0,426.  The value of tobserved = 4,550 > ttable = 0,254 and Sig.0,00 < 0,05.